Axillary recurrence after neoadjuvant chemotherapy: a retrospective study - Castro, Lillian Maria Fernandes de; Lima, Marina Silva Camarço; Costa , Rafael Everton Assunção Ribeiro da; Diniz , Thiago Pereira; Vieira , Sabas Carlos (Mastology, 2024)
Introduction: The justification for this study emerged from the need to evaluate the performance of axillary lymphadenectomy in patients with positive sentinel lymph nodes who underwent neoadjuvant chemotherapy. Axillary lymph node dissection is an invasive and potentially morbid procedure designed to achieve complete remission of breast cancer and prevent unnecessary radical surgery. With the omission of the axillary lymphadenectomy, surgical complications are avoided including lymphedema, stress is decreased, and the quality of life improves in these patients. This study aimed to evaluate axillary recurrence in breast cancer patients undergoing neoadjuvant chemotherapy after the omission of radical axillary lymph node dissection in patients with positive sentinel lymph nodes. Methods: A retrospective study was conducted with ten patients from a clinic specializing in cancer diagnosis and treatment in Teresina (PI), Brazil, diagnosed with breast cancer from January 1998 to February 2021. These patients had positive sentinel lymph nodes and did not undergo axillary node dissection after neoadjuvant chemotherapy. Results: The median patient age at diagnosis was 52 years. All of them had clinical axillary involvement and received neoadjuvant chemotherapy regimen with doxorubicin, cyclophosphamide, and paclitaxel. In addition, they all received adjuvant radiotherapy in the postoperative period and the mean number of sentinel lymph nodes (SLN) removed was two. At a median follow-up of 39.5 months, there was no axillary recurrence and 90% of the patients were alive. Conclusions: At a median follow-up of 39.5 months none of the patients presented axillary recurrence.